(untitled) (Jurnal Pembangunan Sosial, 2020)
This paper aims to discuss the importance of social support in developing healthy aging among elderly in institutions. It covers a discussion on the factors that are required to define the availability of social support for the elderly and what kinds of support systems needed in order to maintain healthy aging. Realizing about the limitation of support system available for elderly in institutions, this paper also includes the discussion on factors that inhibits social support among this marginal group and provides strategies and intervention on how to enhance the availability of social support for this population.